PEMANFAATAN MEDIA PEMBELAJARAN ONLINE PADA MATA PELAJARAN PAI DENGAN MODEL HYBRID LEARNING - Rohman, Taufikur; Khojir, Khojir; Afendi, Achmad Ruslan (ANDRAGOGI, 2022)
Due to the large spread of Covid-19 in Indonesia, the learning process is only limited to face-to-face interactions in locations with a high incidence of infection spread. To accommodate students who attend face-to-face in class or who attend online, teachers can take advantage of online learning media using hybrid learning. The purpose of this study is to explain how to use online learning resources in PAI subjects using a hybrid learning approach. This research is a literature study with a qualitative descriptive approach with data sourced from the library as a source of information, then the data is analyzed using content analysis. The results of this study indicate that PAI teachers can take advantage of various online learning media platforms, including WhatsApp, Google Classroom, and Zoom Meeting. Teachers can use accessible capabilities to deliver information or materials, monitor attendance, and evaluate students participating in online learning.